Editorial bodies : perfection and rejection in ancient rhetoric and poetics - Kennerly, Michele (The University of South Carolina Press, 2018)
A study that reveals the emergence and endurance of vocabularies, habits, and preferences that sustained ancient textual cultures.
Keywords: Rhetoric, Ancient.; Manuscripts -- Editing.; Rhétorique ancienne.; Manuscrits -- Édition.; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing.; LANGUAGE ARTS & DISCIPLINES -- Rhetoric.; REFERENCE -- Writing Skills.; Manuscripts -- Editing; Rhetoric, Ancient